Theory and practice of informed consent in the Czech Republic - Krizova, Eva; Simek, Jiri (Journal of medical ethics, 2007)
The large-scale change of Czech society since 1989 has involved the democratic transformation of the health system. To empower the patient was one important goal of the healthcare reform launched immediately after the Velvet Revolution. The process has been enhanced by the accession of the Czech Republic to the European Union and the adoption of important European conventions regulating the area. The concept of informed consent and a culture of negotiation are being inserted into a traditionally paternalistic culture. Our article describes the current situation on the issue of the communication of information on state of health and treatment, and on the question of the participation of the patient in decisions on treatment. We present empirical results of a public opinion survey on this issue. The results show a still prevailing submissive attitude towards the physicians, despite the fact that the concept of informed consent has become more and more publicly familiar (42% of respondents gave the completely correct answer regarding informed consent). The impact of age, education and sex on answers to the questionnaire was analysed. Men, younger and more educated respondents were more likely to show the autonomous attitude, whereas women, older and less educated people tended to show the traditional submissive attitude. Further, our article raises the question of the cultural and historical background within which the current ethically and legally binding norms (products of western democracies, in fact) are interpreted. The question is how far cultural modifications are tolerable in the practical implementation of universal ethical constructs (informed consent).
Keywords: dospělí; Informed Consent; Physician-Patient Relations; průzkumy a dotazníky; Female; Personal Autonomy; postoj zdravotnického personálu; Adult; ženské pohlaví; Surveys and Questionnaires; moc (psychologie); lidé; Aged, 80 and over; Attitude of Health Personnel; poskytování zdravotní péče; Delivery of Health Care; Power, Psychological; Male; Aged; Czech Republic; osobní autonomie; Česká republika; lidé středního věku; informovaný souhlas pacienta; senioři nad 80 let; senioři; mužské pohlaví; vztahy mezi lékařem a pacientem; Middle Aged; Humans